2005
DOI: 10.1021/jp052822u
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation Number-Based Degrees of Counterion Dissociation in Sodium n-Alkyl Sulfate Micelles

Abstract: Values of the degree of counterion dissociation, R, for sodium n-alkyl sulfate micelles, denoted by SN c S, where N c is the number of carbon atoms in the alkyl chain, are defined by asserting that the aggregation number, N, is dependent only on the concentration, C aq , of counterions in the aqueous pseudophase. By using different combinations of surfactant and added salt concentrations to yield the same value of N, R can be determined, independent of the experimental method. Electron paramagnetic resonance m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 48 publications
4
21
0
Order By: Relevance
“…All the values of the counter ions bound are listed in the Table-1 for all the systems of CTAB and SDS with PEG (different concentration and molar mass). β values obtained for aqueous solution of SDS and CTAB are 0.593 and 0.71, respectively are according to the earlier reported literature values 33,42,43 . β value decreases with the addition of PEG to the aqueous solution of SDS, also with increase in concentration and molar mass of PEG decrease the β as reported 35 which mean that micellization of SDS is enhanced and actually with the addition of PEG, CMC of SDS decreases as observed here and by other 25 .…”
Section: Determination Of Critical Micelle Concentration (Cmc) and Insupporting
confidence: 88%
See 1 more Smart Citation
“…All the values of the counter ions bound are listed in the Table-1 for all the systems of CTAB and SDS with PEG (different concentration and molar mass). β values obtained for aqueous solution of SDS and CTAB are 0.593 and 0.71, respectively are according to the earlier reported literature values 33,42,43 . β value decreases with the addition of PEG to the aqueous solution of SDS, also with increase in concentration and molar mass of PEG decrease the β as reported 35 which mean that micellization of SDS is enhanced and actually with the addition of PEG, CMC of SDS decreases as observed here and by other 25 .…”
Section: Determination Of Critical Micelle Concentration (Cmc) and Insupporting
confidence: 88%
“…Two types of opposing forces are responsible for micellization of ionic surfactant: (a) Favors micelle formation i.e., responsible for the removal of hydrocarbon chain from water matrix (b) Disfavors micelle formation i.e., arises due to the electrostatic repulsion among the similar charged head groups. Measurement of counter ions bound (β) to the micellar interface is basically decreasing the opposing force of charged head groups and increasing the favor of micelle formation 41,42 . Counter ion bound can be obtained from degree of micelle ionization (a) i.e., β = (1 -α), while degree of micelle ionization is obtained from the ratio of the post micellar slope (S2) to the pre micellar slope (S1) from the conductance vs. concentration curve of the surfactant.…”
Section: Determination Of Critical Micelle Concentration (Cmc) and Inmentioning
confidence: 99%
“…It is intriguing to consider that the solubility temperature behavior might yield insight into the difference between the micellar structure and behavior of CsDS and SDS. It is worthwhile to point out that even the simple compact spherical SDS micelle structure has detailed structure of interest and that changes with ionic strength and concentration …”
Section: Resultsmentioning
confidence: 99%
“…At moderate-to-low micelle concentrations and moderate ionic strengths (<0.3 M), SDS forms spherical micelles [20][21][22][23]. Additionally, there is a wealth of information characterizing SDS micelles in aqueous solution at different ionic strengths [20][21][22][23][24][25][26][27][28][29]. Diffusion coefficients of SDS micelles in solution have been measured using both Taylor dispersion [30][31][32][33] and quasi-elastic light scattering [23,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…These studies used methods such as quasi-elastic light scattering, equilibrium ultracentrifugation, steady state fluorescence quenching, time-resolved fluorescence quenching (TRFQ), and small-angle neutron scattering. TRFQ, in particular, has been used to measure the aggregation behavior of SDS in water at various ionic strengths, for a variety of probe and quencher pairs [20,[25][26][27]29,42]. Nolan et al [43] demonstrated that TRFQ can also be applied in fibrous gels if the convolution kernel is modified slightly, and used it to measure aggregation numbers of several nonionic C 12 E m micelles in agarose gel.…”
Section: Introductionmentioning
confidence: 99%